The role of School Administration in the process of managing Distance Learning through the Microsoft Teams Program in following up Teachers in the State of Kuwait - Al-Enzi, Badr Oqlah (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the role of school administration in the process of managing distance learning through the Microsoft Teams program in following up teachers in the State of Kuwait, and the descriptive analytical approach was used through the development of a questionnaire distributed to (74) teachers, who were chosen in a simple random way. The results showed that:- The role of school administration in the process of managing distance learning through the Microsoft Teams program in monitoring teachers from the teachers ’point of view in the State of Kuwait was of a moderate degree, where the arithmetic mean was (3.35), with a moderate degree of appreciation, and the student field came first. With an arithmetic mean (3.67), and a medium degree, followed in second place by the teacher's field with an arithmetic mean of (3.22), and with a moderate degree of appreciation, and in the third place came the field of means and technical tools with an average of (3.16), with a moderate degree of appreciation.- There are no statistically significant differences for the responses of the study sample on the areas of the school administration's role in the process of managing distance learning through Microsoft Teams in the follow-up of teachers. Uniforms for variables of gender, academic qualification and years of experience.Based on the findings of the study, the researcher recommends enriching teacher training programs in universities with courses related to distance learning, the use of computers and the Internet in education, and providing the moral and financial support necessary to spread the culture of using information and communication technology in the school community.
Keywords: School Administration; Distance Learning; Microsoft Teams; Teachers; Kuwait